Zeke Proctor : Cherokee Outlaw - Conley, Robert J. (New York Pocket Books, 1994)
The Spur Award-winning author of Geronimo brings a unique voice to the western novel--the voice of an Indian. A Cherokee himself, Conley now tells the story of Zeke Proctor, a Cherokee veteran of the Civil War, and the only person to ever sign a peace treaty with the U.S. government.
Keywords: Cherokee Indians